Use of sports nutritional supplements in elite rowers: difference between national and international. - López-Dominguez, R.; Sánchez-Oliver, A. J. (Nuevas Tendencias en Educacion Fisica, Deporte y Recreacion, 2018)
The purpose of this study was to compare nutritional supplementation in national and international elite rowers. The sample consisted of 20 elite rowers (23.2 years±3.1), 4 women and 16 men, belonging to the Spanish Absolute Rowing Team. By a tetrapolar electrical bioimpedance, the anthropometric data of the sample were obtained. Through a questionnaire, previously validated, data relevant to the consumption of sports nutritional supplements (SND) were acquired. Values were obtained for height (1.84±0.08 m); weight (81.4±9.9 kg); and fat percentage (16±4.5%). 100% sample answered to have consumed some type of SND, and significant differences were found (pd »0.005, Ô=3.155) between national subjects (n=5) (7.6 SND per subject) and international subjects (n=15) (17.87 SND per subject). The most consumed SND were: iron (85%), caffeine (85%), beta alanine (85%), energy bars (85%), vitamin complexes (80%) and isotonic drinks (80%). There is a high consumption of SND by the sample, mainly international. 100% respects the legality of the supplements consumed and the main purpose of its use was to improve its athletic performance. It is important to promote the effective and efficient use of SNDs, through greater control, and informing athletes about the risks that may arise from their use.